Smoking history, alcohol consumption, and systemic lupus erythematosus: a case-control study. Issue 8 (1st August 1998) - Hardy, Carolyn J; Palmer, Benedict P; Muir, Kenneth R; Sutton, Alex J; Powell, Richard J
Abstract : OBJECTIVE: To investigate the effect of smoking on the development of systemic lupus erythematosus (SLE), and the association between alcohol consumption and the disease. METHODS: 450 subjects (150 SLE patients and 300 controls) from Nottingham, UK were interviewed in a case-control study. Controls were matched to cases for age and sex. All patients met at least four of the American Rheumatology Association criteria for SLE. Controls were randomly selected from the Nottingham Family Health Services Authority register. Information was collected by interview administered questionnaire concerning demographic variables, smoking histories, and drinking habits. RESULTS: Analysis of the data by conditional logistic regression revealed current smokers to have a significantly increased risk of development of SLE compared with never smokers (odds ratio (OR) 1.95, 95% confidence intervals (CI) 1.14, 3.31), although ex-smokers were not at increased risk. There was also suggestion of a marked, highly significant negative association between SLE and alcohol consumption, the magnitude of which increased with units consumed. CONCLUSIONS: This study suggests that current smokers are at increased risk of developing SLE compared with non-smokers and ex-smokers. In contrast, alcohol consumption seems to be negatively associated with the disease.